KOMPRESI DATA TEKS DENGAN METODE RUN LENGTH ENCODING - Umar Mansyuri (Jurnal Ilmiah Sistem Informasi, 2021)
One method of using data compression is by using a method called Run Length Encoding (RLE), especially image data. The RLE method is one of the simplest lossless types of data compression schemes and is based on the simple principle of data encoding. The RLE method is very suitable for compressing data containing repetitive characters such as simple graphic images. The compressed data are 28 RGB (Red, Green, Blue) images and 28 grayscale images in jpg, png, bmp, and tiff formats, respectively. Image data is compressed with an encoder and decoder program using the RLE algorithm in the matlab application. The RLE method is said to be effective in compressing image data if the compression ratio is less than 100% because it has a lot of color repetition in the pixels. The RLE method is said to be ineffective if the compression ratio is more than 100% because it has a little repetition of colors in the pixels. Of the 28 RGB images tested, it was found that the RLE method was effective on 1 image and not effective on 27 images. For the 28 grayscale images tested, it was found that the RLE method was effective on 6 images and not effective on 22 images